Chemical and physical properties of carbonated hydroxyapatite affect breast cancer cell behavior. (15th September 2015) - Choi, Siyoung; Coonrod, Scott; Estroff, Lara; Fischbach, Claudia
Graphical abstract: Abstract: Breast microcalcifications are routinely explored for mammographic detection of breast cancer and are primarily composed of non-stoichiometric hydroxyapatite (Ca10− x (PO4 )6− x (CO3 ) x (OH)2− x ) (HA). Interestingly, HA morphology and carbonate substitution vary in malignant vs. benign lesions. However, whether or not these changes (i) are functionally linked and (ii) impact malignancy remains unclear due in part to lack of model systems that permit evaluating these possibilities. Here, we have adapted a 96 well-based mineralized culture platform to investigate breast cancer cell behavior in response to systematic changes in the chemical and physical properties of HA. By adjusting the carbonate content of the simulated body fluid (SBF) solutions used during growth, we can control the morphology and carbonate substitution of the deposited HA. Our results suggest that both the combined and individual effects of these differences alter breast cancer cell growth and secretion of tumorigenic interleukin-8 (IL-8). Consequently, changes in both HA carbonate incorporation and morphology impact the behavior of breast cancer cells. Collectively, our data underline the importance of biomineralized culture platforms to evaluate the functional contribution of HA material properties to the pathogenesis of breast cancer. Statement of Significance: Breast microcalcifications are small mineral deposits primarily composed of hydroxyapatite (HA). HA physicochemical properties have been of considerable interest, as these are often altered during breast cancer progression and linked to malignancy. However, the functional relationship between these changes and malignancy remains unclear due in part to lack of model systems. Here, we have adapted a previously developed a 96 well-based culture platform to evaluate breast cancer cell behavior in response to systematic changes in HA properties. Our results demonstrate that changes in HA morphology and carbonate content influence breast cancer cell growth and interleukin-8 secretion, and suggest that characterizing the effect of HA properties on breast cancer cells may improve our understanding of breast cancer development and progression.